Cerebral Microbleeds With Atrial Fibrillation After Ablation Therapy - Hirata, Yoshinori; Kato, Natsuko; Muraga, Kanako; Shindo, Akihiro; Nakamura, Naoko; Matsuura, Keita; Ii, Yuichiro; Shiga, Mariko; Tabei, Ken-ichi; Satoh, Masayuki; Fukuma, Tomoyuki; Kagawa, Yoshihiko; et al. (Frontiers in Cellular Neuroscience, 2022)
Background: The prevalence of cerebral microbleeds (CMBs) is significantly higher in patients with atrial fibrillation (AF) than in those without AF. CMBs in patients with AF have been reported to be primarily of the lobar type, but the exact cause of this remains unknown. We investigated the possibility that hemorrhagic transformation of embolic microinfarction can account for de novo lobar CMBs. Methods: A total of 101 patients who underwent ablation therapy for AF were prospectively registered, and 72 patients completed the assessment with MRI 6 months after catheter ablation. Brain MRI, including diffusion-weighted imaging (DWI) and susceptibility-weighted imaging (SWI), were examined at 1–3 days (baseline) and 6 months after catheter ablation. We quantitatively evaluated the spatial and temporal distribution of embolic microinfarctions and de novo CMBs. Results: Of the 101 patients, 68 were enrolled in this study. Fifty-nine patients (86.8%) showed embolic microinfarctions on baseline DWI immediately after catheter ablation. There were 137 CMBs in SWI, and 96 CMBs were of the lobar type. Six months later, there were 208 CMBs, including 71 de novo CMBs, and 60 of 71 (84.5%) were of the lobar type. Of the 71 de novo CMBs, 56 (78.9%) corresponded to the location of previous embolic microinfarctions found on baseline DWI. The platelet count was significantly lower and hematocrit/hemoglobin and Fazekas score were higher in the group with de novo CMBs than in the group without de novo CMBs. Conclusions: De novo CMBs frequently appeared after catheter ablation therapy. Our results suggest that embolic microinfarction can cause lobar CMBs.